2016
DOI: 10.18806/tesl.v33i1.1226
|View full text |Cite
|
Sign up to set email alerts
|

EAP Curriculum Alignment and Social Acculturation: Student Perceptions

Abstract: As factors in facilitating student social and psychological acculturation, the role played by teachers of English as a Second Language (ESL) and the ESL instructional content they deliver are widely acknowledged. Studies across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Research has examined whether EAP programs fulfill students' needs in preparing them to meet the challenges of mainstream university for graduate studies (Terraschke & Wahid, 2011), undergraduate studies (Cheng & Fox, 2008;Evans & Green, 2007;Tweedie & Kim, 2015), or both gradu-VOLUmE 34, iSSUE 2, 2017 ate and under graduate studies (Dooey, 2010;Floyd, 2015;Fox, Cheng, & Zumbo, 2014). For example, two studies explored post-EAP students' perceptions by interviewing them in their first university term in Australia (Dooey, 2010) and Canada (Tweedie & Kim, 2015).…”
Section: Meeting Students' Needsmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has examined whether EAP programs fulfill students' needs in preparing them to meet the challenges of mainstream university for graduate studies (Terraschke & Wahid, 2011), undergraduate studies (Cheng & Fox, 2008;Evans & Green, 2007;Tweedie & Kim, 2015), or both gradu-VOLUmE 34, iSSUE 2, 2017 ate and under graduate studies (Dooey, 2010;Floyd, 2015;Fox, Cheng, & Zumbo, 2014). For example, two studies explored post-EAP students' perceptions by interviewing them in their first university term in Australia (Dooey, 2010) and Canada (Tweedie & Kim, 2015).…”
Section: Meeting Students' Needsmentioning
confidence: 99%
“…For example, two studies explored post-EAP students' perceptions by interviewing them in their first university term in Australia (Dooey, 2010) and Canada (Tweedie & Kim, 2015). The participants reported that although the EAP pathway program helped them develop academic skills such as writing, group work, and note taking, it did not help meet their needs in vocabulary and reading (Tweedie & Kim, 2015) or the oral and listening proficiencies that they needed to integrate with local students and participate in class discussions (Dooey, 2010). Participants' desire for opportunities to interact with and learn from locals or previous EAP students, as Tweedie and Kim (2015) point out, highlights the importance of social acculturation.…”
Section: Meeting Students' Needsmentioning
confidence: 99%
See 3 more Smart Citations